O campo é um laboratório para a gestão ambiental - Neli Aparecida de Mello-Théry (Confins)
The environmental management process demands from its agents knowledge, perspicacity and above all, control of procedures and techniques for its realization. Therefore, it requires that their training be based on interdisciplinarity enriched by the lessons that reality provides them. In this way, reality becomes an essential laboratory, vital for understanding the complex processes between nature and society and for understanding different ways of doing management. This methodological essay aims to point out some paths for the elaboration of territorial environmental management plans, covering from the choice of the place to be studied to the final stage of participatory restitution. It also included some testimonials from students involved in academic monitoring